2011
DOI: 10.1103/physrevb.84.075315
|View full text |Cite
|
Sign up to set email alerts
|

Effect of charged dislocation scattering on electrical and electrothermal transport inn-type InN

Abstract: Temperature dependent thermopower and Hall effect measurements, combined with model calculations including all of the relevant elastic and inelastic scattering mechanisms, are used to quantify the role of charged line defects on electron transport in n-type InN films grown by molecular beam epitaxy. Films with electron concentrations between 4 × 10 17 to 5 × 10 19 cm −3 were investigated. Charged point and line defect scattering produce qualitatively different temperature dependences of the thermopower and mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 55 publications
6
49
1
1
Order By: Relevance
“…They found that the electrons are mainly scattered by charged dislocations. 61) The advantage of polarized IR analysis becomes apparent in the study of the scattering anisotropy of carriers. Figure 8(b) shows the broadening anisotropy of the LOPC+ mode.…”
Section: Carrier-scattering Propertiesmentioning
confidence: 99%
“…They found that the electrons are mainly scattered by charged dislocations. 61) The advantage of polarized IR analysis becomes apparent in the study of the scattering anisotropy of carriers. Figure 8(b) shows the broadening anisotropy of the LOPC+ mode.…”
Section: Carrier-scattering Propertiesmentioning
confidence: 99%
“…TD cores consist of point defect complexes (e.g., impurities or vacancies) that have abundant dangling bonds, which form deep acceptors with a space-charge double Schottky barrier around dislocation lines; these acceptor-like negatively charged TDs generate an effective potential field that induces scattering of electrons by Coulombic interactions 4,5 . This "charged TD scattering" severely reduces the number of free charge carriers and thus diminishes electron mobility (μ e ) in epitaxial semiconductor films (e.g., GaAs 4 , InN 6 , GaN 3,7 ). Therefore, the control of charged TD scattering is a key requirement for achieving heteroepitaxial semiconductor films with an electronic grade if homoepitaxy is not available 3,8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Рост пленки InN проходил в азотобогащенных условиях при соотношении потоков элементов III и V групп ∼ 0.8, при этом поток индия на подложку составлял ∼ 0.4 мкм/ч. В образцах 55 и 61 для роста пленок InN применялся метод эпитаксии с модуляцией потока металла (metal-modulated epitaxy, MME), суть которого состоит в попеременном росте в индийобогащенных условиях роста и выдержке поверхности роста под потоком азота [15,16]. Во время подачи потока In на подложку возникают металлобогащенные условия роста, способствующие поверхностной диффузии адатомов.…”
Section: методика экспериментаunclassified